The Effect of Microwave Baking Conditions on the Quality of Biscuits and the Control of Thermal Processing Hazards in the Maillard Reaction - Dong, Lu; Qiu, Caiyi; Wei, Fan; Yu, Zhenting; Zhang, Yan; Wang, Shuo (Frontiers in Nutrition, 2022)
In order to reduce the thermal processing hazards, microwave-baking was extensive used in food thermal processing. In this study, the influence of microwave power and time on the formation of hazards and their precursors, and the correlation between the sensory characteristics and hazards of biscuits were explored. Furthermore, the content of hazards produced by traditional baking and microwave-baking under the same texture level was compared. The results indicated that acrylamide, 5-hydroxymethylfurfural, methylglyoxal, 3-deoxyglucosone content increased linearly with the extension of microwave time (2, 2.5 and 3 min) and microwave power (440, 480 and 520 W). Compared with traditional baking (190℃, 7 min), microwave-baking could succeed to decrease methylglyoxal, 3-deoxyglucosone, acrylamide, and 5-hydroxymethylfurfural content with the decreasing ratio were 360.75%, 30.19%, 30.87%, and 61.28%, respectively, after microwave baking at 440 W for 3 min. And then the relationship between total hazards levels with some heat-induced sensory characteristics were analyzed, the correlation between sensory characteristics and the formation of hazards is L*>a*>hardness>AW. The correlation coefficients between L* value and the four thermal processing hazards are 0.950, 0.891, 0.803, and 0.985, which can provide a usefulness method to predict the potential hazardous substances levels in microwave-baking biscuits.